Formation hybride vs. présentielle en langues : effets sur la perception des apprenants liés au mode de formation et à l'encadrement pédagogique - Elke Nissen (Recherches en didactique des langues et des cultures)
This study aims at identifying invariants in the way learners perceive the (non) mediation and the tutoring of their course. Our survey and analysis is based on two modalities: the type of learning (blended vs. face-to-face) and the tutor (tutor 1 vs. tutor 2); each tutor participated in both types of learning. The learners responded to questionnaires (N= 104) and this, regarding the blended learning design, two years in a row. This allowed us to also observe the stability of learner perception over time. The questionnaires were evaluated statistically (answers were on Likert scales) and qualitatively (for open-ended questions). Only one of the initial hypotheses, based on a preliminary study, could be confirmed: learner motivation depends on the tutor as well as on the course design and student characteristics. However, what the learners consider to be a “well designed” course varies from one year to the next and does not always refer to the same degree of mediation. On the whole, most variables depend on the tutor, several depend as much on the tutor as on the degree of mediation, a few depend only on the degree of mediation, and some, e.g. the general statement on the course, change from one year to the next.